Pelatihan Character Building untuk Anak Remaja di SMK PGRI 31 Legok Tangerang - Canggih Gumanky Farunik; Puti Lenggo Ginny (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
Character building or character formation is an urgent need in the midst of these conditions. Character formation is an effort to instill positive values ​​such as honesty, responsibility, discipline, cooperation and empathy in individuals, especially the younger generation. This character building training was carried out at SMK PGRI 31 Legok Tangerang, and it was found that based on the post test results it was found that of the 41 respondents, it was known that 57.1 percent did not know themselves well. However, 92.9 percent know well what they like and what they can do. This means that they are able to recognize themselves in the outer layers of themselves, such as understanding potential and tastes. Capital is very important for self-knowledge. Apart from that, it was recorded that 61 percent of participants already knew their life goals.